2023
DOI: 10.3390/ph16030437
|View full text |Cite
|
Sign up to set email alerts
|

Pentosan Polysulfate Affords Pleotropic Protection to Multiple Cells and Tissues

Abstract: Pentosan polysulfate (PPS), a small semi-synthetic highly sulfated heparan sulfate (HS)-like molecule, shares many of the interactive properties of HS. The aim of this review was to outline the potential of PPS as an interventional therapeutic protective agent in physiological processes affecting pathological tissues. PPS is a multifunctional molecule with diverse therapeutic actions against many disease processes. PPS has been used for decades in the treatment of interstitial cystitis and painful bowel diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 274 publications
0
4
0
Order By: Relevance
“… 37 PPS shares many properties with heparin sulfate. 38 PPS associated retinal toxicity could be due to an alteration of glycosaminoglycan concentration or activity within the photoreceptor extracellular matrix (ECM) and other ocular tissues with a rich presence of heparin sulfate, such as Bruch's membrane and choroidal blood vessels. 39 Alterations in the photoreceptor ECM have also been implicated in AMD.…”
Section: Discussionmentioning
confidence: 99%
“… 37 PPS shares many properties with heparin sulfate. 38 PPS associated retinal toxicity could be due to an alteration of glycosaminoglycan concentration or activity within the photoreceptor extracellular matrix (ECM) and other ocular tissues with a rich presence of heparin sulfate, such as Bruch's membrane and choroidal blood vessels. 39 Alterations in the photoreceptor ECM have also been implicated in AMD.…”
Section: Discussionmentioning
confidence: 99%
“…Single-factor experiments [21,22,23] primarily considered the effects of three factors on the extraction rate of xylan: extraction temperature, extraction time, and liquid-to-solid ratio. The liquid-to-solid ratios were tested at ve levels: 10:1 mL/g, 25:1 mL/g, 50:1 mL/g, 75:1 mL/g, and 100:1 mL/g, under conditions of a water bath temperature of 40 ℃ and a water bath time of 120 min.…”
Section: Single-factor Experimentsmentioning
confidence: 99%
“…Its molecular structure and function closely align with those of the naturally occurring glycosaminoglycan substances that play a key role in the maintenance and repair of cartilage and connective tissues. PPS exhibits anti-inflammatory, anti-coagulant, and fibrinolytic properties and promotes the synthesis of hyaluronan, making it effective in endorsing cartilage repair, reducing cartilage fibrillation, improving joint function, and alleviating pain associated with OA [117,120]. Some studies have demonstrated that it presents more benefits than PSGAGs when administered IM.…”
Section: Ppsmentioning
confidence: 99%